Updating poverty maps with panel data - Emwanu, T.; Hoogeveen, J.G.; Okwi, P.O. (Elsevier, 2006)
This paper extends the methodology of Elbers, C., Lanjouw, J. O., & Lanjouw, P. (2003). Micro level estimation of poverty and inequality. Econometrica 71(1), 355-364 and presents a low cost approach to arriving at small area welfare estimates for non-census years. The approach requires panel data and the estimation of a relation between per capita consumption from the year of interest and household characteristics from the census year. The method is illustrated for Uganda. It is shown that with the exception of the North progress in rural poverty reduction was broadly shared during 1992-99. Areas with high initial levels of poverty appear to have benefited less from growth.